Evaluation of Interarch Space for Implant Restorations in Edentulous Patients: A Laboratory Technique - Nicolas F. AbuJamra, DDS, MS,1 Minos M. Stavridakis, DDS, MS,2 (Blackwell Synergy, 2000)
This article describes a laboratory procedure for the visual evaluation of interarch space and its effect on implant prosthesis design. The method is applicable to patients presenting with completely edentulous arches. Silicone impression material is used to form a resilient cast and an external mold from an existing denture. The denture is duplicated using autopolymerizing acrylic resin. The duplicate denture and resilient cast are mounted on an articulator. Spatial relationships of anatomic landmarks can be evaluated, and a quantitative evaluation of available space can be made. The duplicate denture can also be used as a surgical template to direct implant placement. Reference tables are provided to serve as guidelines in the correlation between available space and minimum space required for various implant-assisted restorations.